Підвищення рівня екологічності транспортних перевезень на засадах інтелектуалізації транспортних систем - Ладиженський, Е. Д.; Петленко, В. П.; Гриньків, А. В.; Ladyzhenskyi, Е.; Petlenko, V.; Hrynkiv А. (ЦНТУ, 2025)
Публікацію присвячено дослідженню можливостей застосування інтелектуальних транспортних систем для підвищення рівня екологічності транспортних перевезень в умовах прискореного розгортання цифрової трансформації в країні. Підвищення екологічності на засадах використання інтелектуальних транспортних систем обґрунтовано необхідністю забезпечення стандартів якості реалізації логістичних процесів у контексті сталого розвитку транспортних підприємств, які формуються з точки зору захисту навколишнього середовища. The publication is devoted to the study of ways to improve the level of environmental friendliness of transportation. The purpose of the study is to identify the possibilities of using intelligent transport systems to improve the level of environmental friendliness of transportation, as well as to conduct an analytical review of ways to increase the level of efficiency of the use of software tools, intelligent technologies that contribute to reducing the negative impact of business processes of using corporate transport in supply chains on the local environment.
Increasing the Level of Environmental Friendliness of Transportation Based on the Intellectualization of Transport Systems
Keywords: шкідливи викиди; екологічність транспортних перевезень; інтелектуальні транспортні системи; harmful emissions; environmental friendliness of transportation; intelligent transportation systems